Efficacy and Safety of the Dipeptidyl Peptidase-4 Inhibitor Sitagliptin on Atherosclerosis, β-Cell Function, and Glycemic Control in Japanese Patients with Type 2 Diabetes Mellitus Who are Treatment Naïve or Poorly Responsive to Antidiabetes Agents: A Multicenter, Prospective Observational, Uncontrolled Study - Yuya Tsurutani, MD, PhD; Masao Omura, MD, PhD; Yoko Matsuzawa, MD, PhD; Jun Saito, MD, PhD; Mariko Higa, MD, PhD; Matsuo Taniyama, MD, PhD; Tetsuo Nishikawa, MD, PhD (Elsevier, 2017)
Background: Sitagliptin, a dipeptidyl peptidase-4 inhibitor, is widely used in patients with type 2 diabetes. However, the pleiotropic effects of sitagliptin is not well understood. Objective: To assess the clinical efficacy and safety of sitagliptin on atherosclerosis, β-cell function, and glycemic control in Japanese patients with type 2 diabetes. Methods: A prospective observational study of 270 patients with type 2 diabetes mellitus was carried out. Patients (aged 64.3 [12.4] years, body mas index 25.2 [4.3]) with glycated hemoglobin >6.9% (52 mmol/mol) or fasting plasma glucose >130 mg/dL were treated with sitagliptin for 12 months. The primary end point was glycated hemoglobin level changes from baseline to 3 months. The secondary end points included changes in several biomarkers related to inflammation and β-cell function from baseline to 3 months, as well as changes in glycated hemoglobin level from baseline to 12 months. Results: Glycated hemoglobin levels were significantly lower in patients treated with sitagliptin for 3 months than at baseline (8.1% [1.4%]-7.3% [1.2%]) (65 [16.9]-56 [13.1] mmol/mol]) (P < 0.0001), which continued after 12 months (7.4% [1.3%]) (56 [15.2] mmol/mol) (P < 0.0001). In addition, a marker of vascular-specific inflammation, pentraxin-3, and a marker of β-cell function (proinsulin/insulin ratio), respectively, were lower after treatment with sitagliptin for 3 months than at baseline (1.88 [0.78]-1.65 [0.63] ng/mL [P = 0.0038] and 0.20 [0.14]-0.17 [0.11] [P = 0.01], respectively). On the other hand, a biomarker reflecting whole body inflammation; that is, high-sensitivity C-reactive protein level, was unchanged. Adverse events occurred in 14 patients (5.18%). Conclusions: Sitagliptin may have beneficial effects on vascular inflammation and β-cell function in Japanese patients with type 2 diabetes. Pentraxin-3 may be an early predictive marker for detecting the antiatherosclerotic effects of dipeptidyl peptidase-4.